The Investigation of Macro Structure of Composite Material Mixed Rice Husk with Polyurethane as Insulation Material in Fish Cold Storage Boxes - Balkhaya; Irwansyah; Fitriadi, Nuzuli; Yusrizal (Jurnal Inotera, 2024)
This research aims to investigate the macro structure of a composite material mixed with rice husk and polyurethane. Determine the material with the best composition to apply to the cooler or fish storage area. The urgency of this research is the application of appropriate technological concepts to support the cold chain system so that the quality of fishermen's catches can be maintained. One of the efforts made is to make composite materials for insulation from a mixture of rice husks and polyurethane with various composition ratios ranging from 1:0.5 to 1:2 polyurethane-rice husks. The results of the research show that each composition obtains different results. From the macro photo test resultsed it shows that the lowest maximum area is in the 1:2 composition, namely 1:2A 14393, 1:2B 5232, 1:2C 4013. From all the test results, the composition is 1:2 is the most feasible material for making fish cooler box insulation because, this composition does not affect the expansion of the polyol and issocianate reaction